Influence of Temperature and Moisture on the Shelf-Life of Cement Admixed with Redispersible Polymer Powder - Piqué, Teresa María (2016)
The shelf-life of cement blended with redispersible polymer powder (RDP) used in drymix mortars was studied after exposure to an atmosphere of elevated temperature (40 ± 1 °C) and moisture (90 ± 3% RH) simulated in a climate chamber. As RDP samples, ethylene-vinylacetate and carboxylated styrene-butadiene were used. The behaviour of the cement/RDP blends was studied with respect to film formation of the RDPs and the mechanical properties of the resulting mortars. It was found that the presence of RDP decelerates the prehydration of cement in humid environment and thus improves its shelf-life. At the same time, cement triggers a partial premature film formation from RDP powder during aging. Furthermore, mortars containing aged cement/RDP blends retained their mechanical properties much better than mortars casted from cement which had been aged individually. Apparently, RDP can protect cement from rapid aging.